Հայդուկի հավաքական կերպարը - Բաղդասարյան, Սիրուն (ԱրՊՀ հրատ․)
В статье описан собирательный образ армянского гайдука: вид борьбы, стиль одежды, торжественная клятва, их действия по писанным и неписанным законам. Для гайдука большая честь умереть в борьбе, с песней свободы на устах и с пулей в голове. Также отмечено, что в период арцахской войны образы гайдуков стали примером для нынешних бойцов, в результате этого им удалось победить врага превосходящего их в численности несколько раз. This article describes a collective image of the Armenian hajduk: the kind of fight, fashion, solemn oath, their actions according to written and unwritten laws. Hajduk doesn't have a cemetery, it is an honor to die in the fight, with the song of freedom on his lips and with a bullet in the forehead. It is also noted that during the Artsakh war, images of Hajduks became an example for our current fighters, as a result, they were able to defeat the enemy exceeding them in number.
Keywords: Հայոց ցեղասպանություն; Արցախ